The Influence of Financial Literacy, Financial Technology and Hedonistic Lifestyle on Student Financial Behavior - Bunga Alfira; Robith Hudaya (International Journal of Business and Quality Research, 2024)
Student financial behavior is very important considering their strategic role in building a strong economic foundation. This research aims to analyze the influence of financial literacy, financial technology, and hedonistic lifestyle on the financial behavior of students at the Faculty of Economics and Business, Mataram University. By using a questionnaire consisting of 373 sample respondents, this research uses multiple regression analysis techniques with the help of Partial Least Square (PLS-SEM) software. The findings in this research show a positive and significant influence between financial literacy, financial technology, and hedonistic style on the financial behavior of students at the Faculty of Economics and Business, Mataram University. This means that, the higher the financial literacy, use of financial technology, and hedonistic lifestyle of students at the Faculty of Economics and Business, Mataram University, the more impact it will have on increasing good financial behavior.